2010
DOI: 10.1007/s11250-010-9723-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, carcass characteristics and meat sensory evaluation of West African dwarf sheep fed varying levels of maize and cassava hay

Abstract: A study was conducted to determine the growth performance and meat yield and quality of West African dwarf sheep. Twenty rams weighing an average of 15.3 ± 0.79 kg live weight and with an average age of 18 months were allotted at random to five dietary treatments of 0%, 25%, 50%, 75% and 100% maize hay (MH) for a period of 105 days. Dry matter (DM) intake and growth rate of the rams were improved as the level of cassava hay (CH) increased in the diets. Live weight gain varied significantly (P< 0.05) across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
5
14
0
Order By: Relevance
“…The mean values for weight of heart, lungs, liver, spleen and kidneys, which are characterized as red viscera, were 0.160; 0.660; 0.859; 0.171 and 0.132 kg, respectively. When the organ weights are uniform and have an earlier maturation, they are less affected by dietary treatment in a later stage of life (FASAE et al, 2011). Heart (mean of 0.160 kg) and lungs (mean of 0.660 kg) weights are in agreement with other studies (MORENO et al, 2011), demonstrating that these organs maintain the integrity and have priority in the use of nutrients, regardless of their diet.…”
Section: Resultssupporting
confidence: 89%
“…The mean values for weight of heart, lungs, liver, spleen and kidneys, which are characterized as red viscera, were 0.160; 0.660; 0.859; 0.171 and 0.132 kg, respectively. When the organ weights are uniform and have an earlier maturation, they are less affected by dietary treatment in a later stage of life (FASAE et al, 2011). Heart (mean of 0.160 kg) and lungs (mean of 0.660 kg) weights are in agreement with other studies (MORENO et al, 2011), demonstrating that these organs maintain the integrity and have priority in the use of nutrients, regardless of their diet.…”
Section: Resultssupporting
confidence: 89%
“…Dressing percentage on slaughter weight basis ranges from 35 to 46% in this study, which was comparable with the results of 32 to 44% for Farta sheep, local sheep and Horro rams reported by different studies (Zemicael and Solomon, 2009;Aschalew and Getachew, 2013;Chala et al, 2014). On the other hand, lower results for Tigray Highland sheep (Micheale and Yaynshet, 2014) and higher values local sheep, African dwarf sheep and growing Najidi lambs of Saudi Arabia (AL-Saiday et al, 2010;Fasae et al, 2011;Hagos, 2014) for dressing percentage as compared to that obtained in the current study has been reported.…”
Section: Carcass Characteristics Of Begait Sheepsupporting
confidence: 87%
“…The serum biochemical parameters differed (p<0.05) across dietary treatments. The serum protein compare favourably with values reported for WAD sheep by Fasae et al (2011). The values of serum electrolytes of sodium, potassium, phosphorus and chlorine fell within the normal range (Borjesson et al, 2000) for healthy sheep.…”
Section: Resultssupporting
confidence: 65%
“…Feed conversion ratio as observed in the results of this study showed significant differences across dietary treatments with diets containing 20% CL meal having the best which ranked the same with rams fed 0 and 30% CL meal diets. Higher FCR values of 12 -13 were reported by Fasae et al (2011) in WAD sheep fed maize and cassava hay.…”
Section: Resultsmentioning
confidence: 77%